IMPLEMENTASI ILMU NAHWU DAN SHARAF DALAM PEMBELAJARAN KITAB FATHUL QARIB DI MADRASAH DINIYAH - Muhammad Thobib; Noor Amirudin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The science of nahwu and sharaf are two branches of Arabic language science, likened to nahwu as the father and sharaf as the mother of Arabic language science and both are considered the most important as a tool to be able to read bare books (non-characteristic), one of which is the book fathul qarib. In its implementation at the Madrasah Diniyah Pondok Pesantren Raudhatul Muta'allim Gresik Foundation, these two sciences are in great demand among students because they have very good values. For this reason, this study aims to find out how the implementation of nahwu and sharaf sciences in learning the book fathul qarib at Madrasah Diniyah Pondok Pesantren Raudhatul Muta'allim Gresik Foundation. While the method in this research uses a qualitative approach, by collecting data through interviews, observation, and documentation. The results of this study are 1) the ustad/ustadzh first explains the material of nahwu and sharaf in a simple, easy and light way; 2) the ustad/ustadzh read the book of fathul qarib and the students imitated and gave meaning using Arabic pego; 3) the students read the book fathul qarib one by one and explain its meaning; 4) the ability to explore in its implementation, students can provide conclusions about nahwu and sharaf science material using their own language, to make it easier to study the book of fathul qarib.